Evaluation of Managers' Entrepreneurial Skills and Their Impact on Organizational Productivity in Selected Retail Store in Bulacan Philippines - Esmeralda, Angel (Pusat P2M Politeknik Negeri Batam, 2025)
The comparative study between manager’s entrepreneurial skills and organizational productivity perceives a situation as fair when they obtain equivalent results for similar inputs, in accordance with the equity idea. The study aimed to assess the manager’s entrepreneurial skills towards organizational productivity of selected convenience store in Bulacan and used correlation with descriptive – quantitative design. Findings revealed that there were more female, 51.0 percent, more were in the age from 14 to 60 years old with 58.0 percent, in married category with 60.0 percent, with educational attainment College Graduates with 48.0 percent, in line managers has 52.0 percent. Data showed the average mean of all factors of work performance was 3.47 (SD = 0.52) facing as very highly skilled. The organizational productivity with an overall mean of 3.45, (SD = 0.51), with an interpretation of Very High Productive. This result will be guided that will provide continuous service and implementing flexible working policies to accommodate themselves to competition, often apply different working status together to achieve targets.